THE CULTURAL LANDSCAPE OF GEORGIA: FOR A PARTICULAR BORDERLINE OF THE GEORGIAN SITES SAFEGUARD - Bianca Gioia Marino (European Scientific Journal, ESJ, 2014)
As the UNESCO Recommendation on the Historic Urban Landscape (HUL) of 2011 states, the «urban heritage, including its tangible and intangible components» and it defines the historic urban landscape as an «urban area understood as the result of a historic layering of cultural and natural values and attributes, extending beyond the notion of “historic centre” or “ensemble” to include the broader urban context and its geographical setting». This definition «provides the basis for a comprehensive and integrated approach for the identification, assessment, conservation and management of historic urban landscapes within an overall sustainable development framework». Since the concept of HUL is a ‘hub’ where many aspects and features are mixed and integrated, the Georgian landscape appears to be a significant and typical case: the Georgian culture is characterized by openness and continuous contacts with a lot of Greek, Roman, Iranian, Arabian, Russian and other cultures. This has given the Georgian landscape a specific identity and it offers to the same cultural landscape notion a challenge for his application and working out too (Cultural Landscape Convention, 2000). The main purpose of contribution is about the complexity of the Georgian cultural heritage resources and the particular approach has to be applied in relation to the national cultural programs of conservation and valorization of the Georgian historic urban and natural landscape. This demonstrates that multidisciplinary approach is essential to obtain the conservation of identity and cultural values especially with reference to the management plans which must guarantee that the programs meet with success.